Edible Vaccine: A Prospective Substitute For Better Immunization In Future - RUPALI RAJ KESAR; SUMIT KUMAR; NIDHI; UTTAM KUMAR (International Journal of Pharma and Bio Sciences, 2012)
In this present paper, we make an attempt to insight and assess the methods of preparation, mode of action, advantages, limitations and future prospective of edible vaccines. The study shows that vaccination is a great asset for eradication of infectious diseases in human and animals. Consequently vaccines have reduced mortality rate caused by various infectious organisms. However, vaccines have side-effects on individuals. Recently, a novel approach for developing improved mucosal subunit vaccines has emerged by exploiting the use of genetically modified plants. Edible vaccines can be better substitutes of the traditional vaccines as they can overcome all the problems associated with traditional vaccines. It involves introduction of pre-determined selected desired genes into plants and further inducing these altered plants to manufacture the encoded proteins.